LANGUAGE OF EVALUATION ON ATTITUDINAL SYSTEM OF LOMBOK TOURISM PROMOTION - Indawati, Dewi Retno; Ekawati, Rosyida (Elite : English and Literature Journal, 2021)
The study is aimed at explaining the representation of Lombok tourism promotional video from YouTube official of Indonesia tourism. It focuses on the use of verbal language. The study is descriptive-qualitative method. The source of data of this study is promotional video entitled Wonderful Indonesia Lombok available at https://www.youtube.com/watch?v=BbkFE_K_t0c. This study used the theory of attitudinal system in appraisal language proposed by Martin and White (2005) to observe the verbal language of evaluation. The result of the study shows that Indonesia tourism promotional video of Lombok emphasizes more on the using of positive attitudinal systems in appraisal language to attract the visitors and highlight Lombok destinations such as nature, culture, and the product of local people. Positive evaluation on appreciation and affect on the attractions expressed the worthiness of the resource to be visited and enjoyed with. There is an absence of judgment evaluation that deals with attitudes to people and the way they behave their character All of the positive evaluation resources merge to be one of the representations of Lombok Island as one of tourism destinations in Indonesia worth to visit.